Efektivitas Ekstrak Tumbuhan Terhadap Bakteri dan Jamur Penyebab Infeksi Pasca melahirkan - Hujjatusnaini, Noor; Muh.amin, Astuti; Nirmalasari, Ridha; Karlina, Siti; Ajiza, Pratisa Deifirera; Saputra, Reski; Pitria, Pitria; Maysaroh, Siti; Yuliyana, Via; Respi, Respi (Universitas Medan Area, 2025)
Postoperative infections, especially after childbirth, remain a serious medical issue as they can lead to complications, delay recovery, and increase antibiotic resistance due to the excessive use of synthetic drugs. Therefore, safer and more effective treatment alternatives, such as the use of natural substances, are needed. This study aims to examine the antimicrobial potential of a combination of Ageratum conyzoides, Mussaenda frondosa, and Acorus calamus extracts in inhibiting the growth of Staphylococcus aureus and Candida albicans, which are common pathogens in postnatal surgical wound infections. The study employed a true experimental method with an antimicrobial sensitivity test design using the maceration technique. Extraction was conducted using 96% ethanol with three concentration variations: 40%, 80%, and 120%, in a 3:2:1 mixture ratio. Phytochemical screening was carried out to identify secondary metabolite compounds, followed by an inhibition test using the disc diffusion method. The results showed that Acorus calamus extract contains flavonoids, alkaloids, and saponins. Ageratum conyzoides, Mussaenda frondosa, and Acorus calamus all contain saponins with potential antimicrobial activity. The combination of these extracts demonstrated inhibitory effects against the growth of pathogenic microorganisms in surgical wounds, as evidenced by the formation of inhibition zones during testing.